(untitled) (Malaysian Management Journal, 2014)
In the recent years, the Muslim international tourists market has become the focus of the tourism industries in the Asia Pacific. Taiwan has also noticed the potential of this market segment, and started promoting its tourism products to the international Muslim tourists. In order to promote Taiwan effectively to this market segment, it is important to identify the factors that influence the perception of the Muslim tourists about Taiwan. With this notion, this study set out to establish the pre-visit tourism image of Taiwan held by the Muslim tourists, and determine the factors that influence the Muslim tourists’ image evaluations. This study employed both structured and unstructured methods in the survey, and the data was analysed using content analysis, factor analysis, and structural equation modeling. The findings indicated that Muslim tourists generally have a positive image of Taiwan; however, this image is fuzzy. Furthermore, the direct effect of travel motivation on affective images was significant, and the ‘Relax’ dimension of travel motivation has the greatest impact. However, the ‘Religious’ dimension of travel motivation did not have significant effect on affective image.